Clinical evaluation of polyherbal formulation (Uricare Tablet) in benign prostatic hyperplasia: randomized, placebo controlled, single blinded clinical study - Patel, Hardik R.; Patel, Manish; Patel, Mansi M.; Patel, Janmjay H.; Patel, Payal G.; Patel, Apurva N. (International Journal of Clinical Trials, 2016)
Background: This was a randomized, placebo controlled, single blinded clinical trial undertaken in 60 male patients in the age group of 18-70 years diagnosed with benign prostatic hyperplasia (BPH) in the department of at P.D. Patel Kayachikitsha, Ayurveda Hospital, India. Methods: A medical history, especially on urinary symptoms was obtained from all patients on first visit along with Blood tests. 60 Patients were randomized into two groups. Uricare tablet was administered at the dose of 2 tablets twice a day for the period of 6 weeks to treatment group and Placebo tablet was administered with same doses to the remaining patients group. They were evaluated on BPH assessment parameters, IPSS (International prostate symptom score), quality of life (QOL), level of serum PSA and the prostate volume. Results: Percentage reduction in IPSS score was observed 25.62% and 1.80% in treatment and placebo group respectively. Percentage improvement in QOL was also observed 31.67% and 2.82% in treatment and placebo groups respectively. BPH assessment parameters also show moderate changes in before and after treatment in both groups. However, the reduction in prostate volume was identified up to -4.612cc and -1.427cc in treatment and placebo group respectively at the end of the trial. Prostate significant antigen (PSA) was significantly reduced in the treatment group than Placebo group. Conclusions:There were no serious adverse effects observed during the study. Hence, the therapy was assumed to be well tolerated by patients and can be considered as a drug of choice in the management of BPH.